1998
DOI: 10.2307/2411092
|View full text |Cite
|
Sign up to set email alerts
|

Virulence of Mixed-Clone and Single-Clone Infections of the Rodent Malaria Plasmodium chabaudi

Abstract: Most evolutionary models treat virulence as an unavoidable consequence of microparasite replication and have predicted that in mixed-genotype infections, natural selection should favor higher levels of virulence than is optimal in genetically uniform infections. Increased virulence may evolve as a genetically fixed strategy, appropriate for the frequency of mixed infections in the population, or may occur as a conditional response to mixed infection, that is, a facultative strategy. Here we test whether facult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
95
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 121 publications
(102 citation statements)
references
References 0 publications
5
95
2
Order By: Relevance
“…Metabolic cost of mounting an immune response and maintenance of a competent immune system has been shown to be high (Sheldon and Verhulst 1996;Nordling et al 1998;Lochmiller and Deerenberg 2000;Moret and SchmidHempel 2000). Moreover, maintaining several different means of defence is likely more costly than sustaining one specific type of defence (Taylor et al 1998), so that hosts subjected to challenges from multiple parasites often prefer to give up their defence and to surrender rather than to spend much energy for defence (Jokela et al 2000). Metabolic cost of testes can be high as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metabolic cost of mounting an immune response and maintenance of a competent immune system has been shown to be high (Sheldon and Verhulst 1996;Nordling et al 1998;Lochmiller and Deerenberg 2000;Moret and SchmidHempel 2000). Moreover, maintaining several different means of defence is likely more costly than sustaining one specific type of defence (Taylor et al 1998), so that hosts subjected to challenges from multiple parasites often prefer to give up their defence and to surrender rather than to spend much energy for defence (Jokela et al 2000). Metabolic cost of testes can be high as well.…”
Section: Discussionmentioning
confidence: 99%
“…This may be especially true when a host is subjected to multiple parasite challenges (Taylor et al 1998). Consequently, a host faces an evolutionary trade-off between investment into energetically demanding anti-parasitic defences and other energetically demanding systems such as development and maintenance of expensive tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a host subjected to multiple challenges from multiple distantly related parasites can either mount stronger immune responses (e.g., Morand and Poulin, 2000;Møller and Rozsa, 2005) and/or increase sharply its grooming effort (e. g., Cotgreave and Clayton, 1994). However, maintaining several different means of defense is likely more costly than sustenance of one specific type of defense (Taylor et al, 1998b). As a result, the effectiveness of energy allocation to immune defense decreases as the diversity of attack types increases (Jokela et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The same means of defense that is effective against one parasite will not necessarily be effective against another parasite (Taylor et al 1998). Therefore, for a host inhabiting parasite-rich habitats, it should be advantageous to have the ability to cope with multiple challenges, especially if the probabilities to be attacked by different parasites are similar, although maintenance of multiple defense means is likely to be much more costly than retaining a specific type of defense (Taylor et al 1998). Nevertheless, both species in our study demonstrated similar immune responses to antigen from an unfamiliar flea species, in spite of different species richness of their natural flea assemblages.…”
Section: Immune Response and Diversity Of Parasitesmentioning
confidence: 99%
“…Maintaining several different means of defense is likely more costly than sustenance of one specific type of defense (Taylor et al 1998). Consequently, host species that are exploited by a small number of specific parasites can acquire specific immune resistance against these parasites but not against other, albeit phylogenetically related parasites.…”
Section: Introductionmentioning
confidence: 99%